Overreaction, Underreaction, and Price Earnings Ratio Stock Anomaly at Jakarta Stock Exchange - Rahmawati Rahmawati; Christiyaningsih Budiwati (Jurnal Akuntansi dan Bisnis, 2007)
This research examines the overreaction hypothesis in manufacturing company at Jakarta Stock Exchange (JSX) between years 2000 to 2002. The overreaction hypothesis predicts that securities suffering abnormally low return (losers) will subsequently experience abnormally high return. On the contrary, securities with abnormally high return (winners) will later experience abnormally low return. The overreaction hypothesis also stated that investor overreact in the initial period and subsequently correct themselves or people tend to overweight recent information and to underweight prior data. The sample obtained by using market adjusted model amounted to 15 loser stocks and 15 winner stocks. The results of this research seem to indicate that overreaction occurs separate in its move. Winners and losers are not constant overtime. Analysis independent sample t test, winners and losers do not show the different average abnormal return significantly. Implication on the efficient market hypothesis is the phenomena of overreaction shows that market is not efficient (especially Jakarta Stock Exchange), since the stock price can be predicted on the previous stock price. PER anomaly seems to low PER stock will better have high return than high PER stock.